Tradition and Sprituality: Cultural Symbolism of Papuan Bakar Batu and Korean Chuseok - Ambarita, Jenri; Siahaya, Agusthina; Sari, Uci Purnama (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
Papua and Chuseok from South Korea, within a global context, employing Clifford Geertz's theory of cultural symbolism. Bakar Batu is a deeply rooted culinary and communal ritual in Papua, bringing people together in a shared act of cooking that honors ancestral spirits and nature. In comparison, Chuseok is a Korean harvest festival that celebrates gratitude for the year's abundance and includes ancestral rites and communal sharing of traditional foods. This study uses a qualitative approach to examine the symbolic meanings embedded in these two traditions through literature review and thematic data analysis. The findings reveal that, despite the forces of globalization and modernization, both Bakar Batu and Chuseok uphold collective identity and spiritual values, illustrating Geertz's perspective that symbols embody culture and reinforce social unity and cultural continuity. Each tradition, while evolving, remains resilient in preserving its symbolic meaning, underscoring the global relevance of cultural rituals in affirming identity, fostering community solidarity, and transmitting spiritual values across generations. This study contributes to global discourses on cultural preservation, emphasizing the universal role of ritual in sustaining identity and social cohesion amidst diverse cultural landscapes.